Efficacy of Er: YAG laser in Removing of Calcium Hydroxide Dressing from Root Canals (Journal of Hama University, 2020)
Aim of study was to evaluate the efficiencies of Er: YAG laser in two powers in removing Calcium Hydroxide dressing comparing with passive ultrasonic irrigation. 30 single-root were prepared to size F2 with ProTaper rotary system and split longitudinally. Two standardized grooves were prepared into the apical and coronal part of the root canal dentine. The roots were subsequently reassembled with wires and filled with calcium hydroxide. Then they were stored in 100% relative humidity for 1 week. Specimens were randomly divided into 3 experimental groups (n=10) according to removal technique.  In-group 1:ـEr: YAG: laser using0.5 w for 50 sec.  Group 2:ـEr:YAG :using1 w for 30 sec. Group 3:ultrasonic system used passively for 60 seconds with 5 ml of 5.25% NaOCl. The quantity of remaining of Calcium Hydroxide were observered under a stereomicroscope with 30 magnification as described by van der Sluis et al. (2007).  Statistical evaluation was performed using Kruskal-willsand Wilcoxon tests. Results showed that Er: YAG laser was effective in calcium hydroxide removal in the apical and coronal grooves but there was no significant difference between Groups.